Educação autóctone tradicional e a educação oficial moderna : efeitos dos ritos de iniciação autóctone sobre o rendimento escolar dos alunos iniciados - Canda, Candido Jasse (2006)
The presente research studies lhe impact of traditional native education on a modem official education in lhe scope of initiations rites effects upon school achievement of lhe pupils initiated It aims to identifyeducational effects embedded in the traditional native education through. initiatian rites that influence school achievement afilie pupils initiated. The methods and means of transmissionof knowledgeapplied in the native education, are at lhe core of this research in an attemptto assess their effectivenessin the building of personalityand bringing up new moral and ethic values fostering scholl achievementofthe initiated youngsters. The study of educationalimpact acknowledgesthat lhe subjects of lhe study are a racional species that owns culture. The study outcomes highlight that: 1. Tradionalcommunitiesexpress great worry about lhe official school effectivinessregarding lhe basic education for lhe new generations.The fact of official school beeing under govermmentinhbits lhe communitiesto overtly express their opinion in lhe relation no matter for jt is taken for granted that what is under stat contrai mnst be honorably and full carried out. This situationtums the apparentconflictbetween native education and official educationinto a longstandingconflictbetweenlhe two educationalsystems is a social and cultural imperative. 2. Teachers,as those who put into efectlhe modem educationpolicies are awãte of lhe relevanceof some educationalaspects of native education,but due rigidity of lhe official education,there is no roam for teachersinitiativeswhen carrying out official teachingand leaming programs